Estudo da dinâmica populacional e interações biológicas de Dendrocephalus brasiliensis (Pesta, 1921) em ambientes experimentais - Paccagnella, Yeda Carolina (2012)
The planet Earth is facing a serious crisis of the biodiversity loss. Often, human activities are responsible for biological invasions that alter significantly the various ecosystems and could lead to the extinction of native species. Dendrocephalus brasiliensis ( branconeta ) is a native freshwater Anostraca species, which has been studied and used in aquaculture to replace the brine shrimp originating from saline environments. Its occurrence in natural environments was recorded in Brazilian southeast and northeast regions, from the city of Urucuia-MG to Piauí State. However, there are records of its accidental introduction into fish ponds in São Paulo state, cities of Tabatinga and Arealva. The goal of this work is the study of the interactions of competition and predation / herbivory between D. brasiliensis and other planktonic species native of São Paulo in order to assess the possible impacts of a possible introduction of this species in natural environments where it does not occur originally. This study was conducted in an experimental system (10.000L tank) in Aquaculture Station of Department of Hydrobiology (EA-DHb), Federal University of São Carlos (UFSCar), São Carlos, SP, Brazil. Initially, the experimental tank was inoculated with the green algae Pseudokirchneriella subcapitata grown in laboratory. After the establishment of phytoplankton, zooplankton species were collected in limnic ecosystems of São Paulo state, in particular near São Carlos (June and July/2011), for the establishment of a zooplankton community in the experimental tank. Zooplankton succession in the tank was monitored for 133days before the introduction of branconeta. To evaluate the interaction of D. brasiliensis with other zooplankton species, the experimental tank was divided in two equal compartments that do not communicate to each other: one of them was kept with the original composition of the zooplankton, while in the other, cysts of the anostracean were introduced. In both experimental compartments samples were collected daily during 39 days, for quantitative and qualitative analyzes of zooplankton community, besides chlorophyll a, physical and chemical variables. The environmental variables were correlated to zooplankton groups using the statistical method of Canonical Correspondence Analysis (CCA). Numerical densities of Cladocera and Copepoda groups decreased in the presence of D. brasiliensis. We can conclude that the presence of D. brasiliensis does not exclude but significantly alters the composition and density of the plankton community.